Rediscovery of the Malay 'local:' youth and TV fiction in Malaysia - Mohd Muzhafar Idrus; Hashim, RS; Mydin, RM (Routledge Journals, Taylor & Francis Ltd, 2024)
Previous research has shown that while TV fiction is coloured with narrative appeals, themes of love and binary opposition (good versus evil, love versus hate and rich against poor), TV producers continue to tailor their products to match audience's pleasure. Such formula may be cliched, but in the world where news of war, terrorism, diseases and conflicts often make the headlines, respite from harsh realities of life can often be found through studying TV fiction. Drawing from theory of cultural hybridity, this article explores how youth relate to three popular Malay TV fiction, On Dhia, Julia and Adam & Hawa through interviews and personal narratives. Their voices have shown forms of rediscovery of the Malay 'local,' providing glimpses into what it means to rediscover Malay local fragments in times of global risks and chaos, oscillating between a wide array of social and cultural uncertainties that continue to unfold for imagination.